A gift of hope [large type] : helping the homeless - Steel, Danielle (Thorndike Press, 2012)
This book tells the story behind bestselling author Danielle Steel's crusade to help the homeless of San Francisco. In her powerful memoir His Bright Light, the author opened her heart to share the devastating story of the loss of her beloved son. In this new memoir, she shows us how she transformed that pain into a campaign of service that enriched her life beyond what she could imagine. For eleven years, she took to the streets with a small team to help the homeless of San Francisco. She worked anonymously, visiting the "cribs" of the city's most vulnerable citizens under cover of darkness, distributing food, clothing, bedding, tools, and toiletries. She sought no publicity for her efforts and remained anonymous throughout. Now she is speaking up to bring attention to their plight. In this memoir, she talks publicly for the first time about her work among the most desperate members of our society. She offers portraits of the people she met along the way, and issues a call for more effective action to aid this vast, deprived population. Determined to supply the homeless with the basic necessities to keep them alive, she ends up giving them something far more powerful: a voice.